Attitudes of Italian Psychiatrists Toward the Evaluation of Physical Comorbidities and Sexual Dysfunction in Patients With Schizophrenia. Implications for Clinical Practice - Monteleone, Palmiero; Amore, Mario; Cabassi, Aderville; Clerici, Massimo; Fagiolini, Andrea; Girardi, Paolo; Jannini, Emmanuele A.; Maina, Giuseppe; Rossi, Alessandro; Vita, Antonio; Siracusano, Alberto (Frontiers in Psychiatry, 2019)
Treatment guidelines for patients with schizophrenia recommend evaluating their risk of physical comorbidities, especially since these patients are known to have decreased life expectancy due to comorbidities. Therefore, to the authors’ knowledge, this is the first national survey conducted to investigate how Italian psychiatrists deal with the risk of physical comorbidities and sexual dysfunction in patients with schizophrenia. A sample of 750 psychiatrists completed an ad hoc online survey investigating their decision making about performing blood tests, clinical and instrumental examinations, and scheduling follow-up appointments in relation to the different phases of the illness and possible pharmacological side effects. Compared to patients in therapeutic continuation, those diagnosed for the first time and those who received a therapeutic change were visited more frequently (every 15 to 17 days vs. every 40 days, respectively), and were more regularly prescribed blood tests and instrumental examinations (every 4.2 to 4.4 months vs. every 9 months, respectively). There was a high interest in the surveillance of cardiometabolic risk. In 54% of patients, prolactin testing was not requested before starting an antipsychotic. In terms of specialist referrals, only 5% of surveyed psychiatrists “never” sought for additional counselling. There was little attention given to sexual functioning assessment based on the survey results about patients’ daily life and with regard to deciding to prescribe additional examinations. In fact, only up to 3% of psychiatrists reported assessing sexual functioning using specific psychometric tests. In summary, this survey describes Italian psychiatrists as careful healthcare providers for the physical illnesses of patients with schizophrenia but with several shortcomings. For instance, clinical attention towards patients’ sexual and reproductive healthcare needs remains a challenge. Psychiatrists should take the lead for the integrated education, assessment, and care of medical needs of their patients with mental illness. Based on the results of this survey, the authors also believe that a future challenge for the management of patients with mental illness will be the classification of patients based on their risk of comorbidities, to help ensure optimal healthcare provision for those at greater risk of other illnesses.